An introduction to the systematics of Akodon orophilus Osgood, 1913 (Rodentia: Cricetidae) with the description of a new species - Jiménez, Carlos F.; Pacheco, Víctor; Vivas, Dan (Zootaxa, 2013)
The genus Akodon is one of the most species-rich rodent lineages in South America. In Peru, this genus contains 14 species subdivided in two groups: aerosus and boliviensis. Akodon orophilus Osgood, 1913 (Rodentia: Cricetidae) is a member of the Akodon aerosus group that inhabits the northern Peruvian montane forest, but is poorly characterized and its distri-bution is vaguely known. We review the status of the species based on morphology, morphometric and karyology, and compared with all members of the Akodon aerosus clade from Peruvian montane forests. As a result, we provide a com-plete redescription of A. orophilus, present new information on its natural history, restrict its distribution to the east of Río Marañón, and describe a new species of Akodon from Huánuco Department, central Peru, a population previously as-signed to A. orophilus.